Meeting between the Prime Minister and members of the Trades Union Congress General Council Special Industrial Committee (9.20 pm) (verbatim report) (1926/04/26) - Trades Union Congress. General Council. Special Industrial Committee ; Baldwin, Stanley Baldwin, Earl, 1867-1947
26 April 1926